Modified heat-resistant PMMA (polymethyl methacrylate) as well as preparation method and application thereof

By melting and mixing PMMA resin, bio-based polycarbonate resin, nano-inorganic compound sodium organic bio-sulfonate ester and additives, a modified heat-resistant PMMA material with high glass transition temperature and good coloring properties was prepared, which solved the problem of insufficient heat resistance at high temperatures in existing modified PMMA materials and achieved efficient temperature deformation resistance.

CN119570185APending Publication Date: 2025-03-07ZHEJIANG KEPUTE NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411777625.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-12-04
Filing Date
2024-12-05
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing modified PMMA materials have insufficient heat resistance at high temperatures and cannot meet the temperature resistance of materials such as automotive trim panels and turn signals, resulting in deformation during use.

Method used

By melting and mixing PMMA resin, bio-based polycarbonate resin, nano-inorganic composite organic bio-based sodium sulfonate ester and additives, a modified heat-resistant PMMA material with high glass transition temperature, good coloring properties and temperature alternating properties were prepared.

Benefits of technology

It has achieved high transparency (light transmittance above 90%), high glass transition temperature (not less than 115℃), good coloring and pencil hardness up to 2H, and has good temperature and deformation resistance, meeting the requirements of automobile factories for heat resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570185A_ABST
    Figure CN119570185A_ABST
Patent Text Reader

Abstract

The invention discloses modified heat-resistant PMMA (polymethyl methacrylate) as well as a preparation method and application thereof in preparation of an automobile material. PMMA resin, a modified material and an auxiliary agent are melted and mixed to obtain the modified heat-resistant PMMA, and the modified heat-resistant PMMA is characterized in that the modified material comprises bio-based polycarbonate resin and nano inorganic matter composite organic bio-based sodium sulfonate ester. The invention mainly solves the problem of insufficient heat resistance, and the prepared modified PMMA heat-resistant material has the following key properties: transparency (light transmittance is more than 90%), high glass transition temperature (Tg is not lower than 115 DEG C), good colorability (easy coloration and no birefringence), pencil hardness of 2H, and good temperature alternating resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to advanced material technology and relates to a modified PMMA, specifically a modified heat-resistant PMMA and a preparation method and application thereof, especially application in materials such as automobile trim panels and turn signals. Background Art

[0002] Polymethyl methacrylate (PMMA), also known as acrylic, acrylic or organic glass, Lucite (trade name), has high transparency and a light transmittance of 92%, which is higher than that of glass; the relative molecular mass of PMMA is about 2 million, and it is a long-chain high molecular polymer, and the chain forming the molecule is very soft. Therefore, PMMA has a relatively high strength, and its tensile and impact resistance is 7 to 18 times higher than that of ordinary glass. It is a commonly used glass substitute material. However, with the increase in the ambient temperature of use, the conventional PMMA heat resistance cannot meet the requirements of the automobile factory's test requirements, so it is necessary to improve the insufficient heat resistance of PMMA. The prior art uses PC combined with a heat-resistant agent to improve the heat resistance of PMMA. CN113278240A discloses a high heat-resistant and high-toughness light-diffusing PMMA alloy material for automobiles and a preparation method thereof. The main ingredients include PMMA resin, SAN resin, silicone / acrylic composite rubber, PC resin, modified light-diffusing agent, compatibilizer, and heat-resistant agent. The prepared modified PMMA has a heat deformation temperature of less than 90°C. PMMA / PC blends are thermodynamically incompatible, and are prone to phase separation and poor adhesion between the two phase interfaces. Not only are the mechanical properties poor, but the composite material is also not transparent (Montaudo G, Puglisi C, Samperi F. Chemical Reactions Occurring in the Thermal Treatment of PC / PMMA Blends [J]. Journal of Polymer Science Part A: Polymer Chemistry, 1998, 36 (11): 1873-1884). The existing technology "Preparation and Performance Research of High Hardness Transparent PC / PMMA Alloy" uses SiO2 / PMMA instead of pure PMMA to modify PC, melts and blends it with PC, and adds ester exchange catalyst SnCl2 to prepare a high surface hardness transparent SiO2-PMMA / PC composite material with a light transmittance of 70.7%, which is similar to 72.8% of PC / PMMA / SnCl2-0.05. It can be seen that although the PC / PMMA system has good application prospects, the heat resistance and optical properties of the alloy material still need to be improved. Summary of the invention

[0003] At present, materials such as automobile trims and turn signals are modified PMMA by spray-free painting, but they cannot meet the customer's requirements for temperature deformation resistance, resulting in deformation during use. The present invention mainly solves the problem of insufficient heat resistance, provides a modified heat-resistant PMMA and its preparation method and application, and prepares the key properties of modified PMMA heat-resistant materials: transparency (light transmittance above 90%), high glass transition temperature Tg (not less than 115°C), good colorability (easy to color and no birefringence), pencil hardness up to 2H, and has good temperature alternating performance.

[0004] The present invention adopts the following technical scheme.

[0005] A preparation method of modified heat-resistant PMMA comprises the following steps: melting and mixing PMMA resin, a modified material and an auxiliary agent to obtain the modified heat-resistant PMMA; the modified material comprises a bio-based polycarbonate resin and a nano-inorganic composite organic bio-based sodium sulfonate.

[0006] In the present invention, the mass ratio of PMMA resin, bio-based polycarbonate resin, nano-inorganic composite organic bio-based sodium sulfonate, and additive is (70-85): (15-30): (0.1-0.5): (0.5-1.5).

[0007] Preferably, the mass ratio of PMMA resin, bio-based polycarbonate resin, nano-inorganic composite organic bio-based sodium sulfonate, and additive is (70-80): (20-30): (0.2-0.4): (0.5-1.5).

[0008] Further preferably, the mass ratio of PMMA resin, bio-based polycarbonate resin, nano-inorganic composite organic bio-based sodium sulfonate, and additive is (70-80): (20-25): (0.2-0.3): (0.6-1.4).

[0009] In the present invention, the modified material consists of bio-based polycarbonate resin and nano-inorganic composite organic bio-based sodium sulfonate.

[0010] In the present invention, the auxiliary agent includes an antioxidant and a weathering agent. Furthermore, according to the need, the auxiliary agent may also include a pigment, such as carbon black, preferably uncarrier carbon black.

[0011] Preferably, the mass ratio of the antioxidant, the weathering agent, and the pigment is (0.8-1.2):(0.8-1.2):(0-1.5).

[0012] Preferably, the mass ratio of antioxidant, weathering agent and pigment is 1:1:(0-1.5).

[0013] In the above ratio, when the pigment is 0, it means that the additive does not contain pigment.

[0014] The invention discloses a modified heat-resistant PMMA prepared by the preparation method of the modified heat-resistant PMMA, which is transparent (light transmittance is above 90%), has a high glass transition temperature (Tg is not less than 115°C), good colorability (easy to color and no birefringence), a pencil hardness of up to 2H, and has good temperature deformation resistance.

[0015] The invention discloses application of the modified heat-resistant PMMA in preparing heat-resistant plastics.

[0016] The invention discloses application of the modified heat-resistant PMMA in preparing heat-resistant transparent materials.

[0017] The invention discloses application of the modified heat-resistant PMMA in preparing heat-resistant PMMA materials.

[0018] The invention discloses application of the modified heat-resistant PMMA in preparing heat-resistant automobile materials.

[0019] The invention discloses application of the modified heat-resistant PMMA in preparing heat-resistant automobile trim panels and turn signal lamp materials.

[0020] The invention discloses a heat-resistant plastic, the preparation raw materials of which include the modified heat-resistant PMMA.

[0021] The invention discloses a heat-resistant automobile material, and the raw materials for preparing the heat-resistant automobile material include the modified heat-resistant PMMA.

[0022] In the present invention, PMMA resin, modified materials and additives are melt-mixed by an extruder. The specific operation is conventional technology, such as using a twin-screw device. After the materials used in the present invention are mixed, they can be directly put into the twin-screw extruder for melt processing, or a single material can be added to the extruder separately through a loss-in-weight metering scale, and the processing aid and carbon black masterbatch are mixed together and added through a single loss-in-weight metering scale; the twin-screw device used can have a diameter of 30-75 mm, a rotation speed of 300-1200 rpm, and a temperature of 210-260° C. for processing, molding and granulation.

[0023] The present invention mainly conducts comprehensive performance modification research on PMMA, including the preparation method and application of modified heat-resistant PMMA, introduces bio-based polycarbonate resin and nano-inorganic composite organic bio-based sodium sulfonate, and prepares a modified heat-resistant PMMA composite material with high surface hardness, transparency (pigment-free), good mechanical and processing properties through a relatively simple and convenient melt blending method. The surface gloss is above 78gloss (at an angle of 20°), the surface blackness reaches the blackness of high-gloss spray paint (L value is below 24.6), the wear resistance is better than that of PMMA material, the heat resistance can meet the requirements of automobile factories, the transparency of PMMA material is not affected, and PMMA is easy to be colored. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a photo of the conventional sample preparation of modified heat-resistant PMMA (carbon black omitted) in Example 1, which has excellent light transmittance.

[0025] Figure 2 This is a photo of conventional sample preparation of modified heat-resistant PMMA in Example 1, which has an excellent high-gloss black effect.

[0026] Figure 3 This is a photo of conventional sample preparation of modified heat-resistant PMMA in Example 1, and no deformation occurs.

[0027] Figure 4 This is a photo of the conventional sample preparation of modified heat-resistant PMMA in comparative example 1, and the glue inlet is deformed.

[0028] Figure 5 This is a photo of conventional sample preparation of modified heat-resistant PMMA in Example 4, and no deformation occurs. DETAILED DESCRIPTION

[0029] Although the PC / PMMA system has good application prospects, the heat resistance and optical properties of the alloy material need to be improved. The present invention conducts comprehensive performance modification research on PMMA, including the preparation method and application of modified heat-resistant PMMA, introduces bio-based polycarbonate resin and nano-inorganic composite organic bio-based sodium sulfonate, and prepares modified heat-resistant PMMA with excellent performance through a relatively simple and convenient melt blending method.

[0030] The invention melt-mixes PMMA resin, a modified material and an auxiliary agent to obtain a modified heat-resistant PMMA; the modified material is a bio-based polycarbonate resin and a nano-inorganic composite organic bio-based sodium sulfonate ester. The auxiliary agent includes an antioxidant and a weathering agent, and further, according to needs, a pigment such as carbon black, preferably carrier-free carbon black, can be included.

[0031] After mixing, the materials used in the present invention can be directly put into a twin-screw extruder for melting processing, or a single material can be added to the extruder separately through a loss-in-weight metering scale, and the processing aid and the carbon black masterbatch are mixed together and added through a single loss-in-weight metering scale; the twin-screw equipment used can have a diameter of 30-75 mm, a rotation speed of 300-1200 rpm, and a temperature of 210-260° C. for processing, molding and granulation to obtain modified heat-resistant PMMA.

[0032] The formula for preparing the modified heat-resistant PMMA of the present invention is as follows: PMMA resin balance Bio-based polycarbonate resin 15-30% Nano inorganic composite organic bio-based sodium sulfonate ester 0.1~0.5% Antioxidant 0.4% Weathering agent 0.4% Uncarrier carbon black 0 or 1-1.5% In the present invention, the bio-based polycarbonate resin is a transparent bio-based polycarbonate resin mainly derived from plant-based isosorbide. It has good colorability, excellent durability, optical properties, excellent scratch resistance and UV resistance, and is suitable as a substitute for high-performance glass components. The present invention uses this as a modifier, combined with nano-inorganic composite organic bio-based sodium sulfonate, not only to improve the heat resistance of the material, but also to maintain good optical properties, especially to improve the high and low temperature alternating performance of the product.

[0033] The following is a specific experiment to illustrate the technical progress of the present invention. The raw materials used in the present invention are existing products, which are specifically described as follows; the specific preparation operations and performance tests are all conventional technologies. Further, the method for preparing the modified heat-resistant PMMA sample of the present invention is a prior art, which does not affect the understanding of the technical effect of the present invention by those skilled in the art.

[0034] PMMA resin: Chimei CM205 was used. The Vicat softening temperature was 104°C, the transmittance was 92%, and the glass transition temperature was 113°C as measured by the following method.

[0035] Modifier No. 1: PC resin, glass transition temperature 140°C, Lotte 1220 from Korea.

[0036] Modifier No. 2: Bio-based polycarbonate resin, glass transition temperature 133°C, Japan Mitsubishi D7340R.

[0037] Modifier No. 3: styrene-methyl methacrylate-maleic anhydride terpolymer, glass transition temperature 128°C; Jiayirong BP-356M.

[0038] Modifier No. 4: PEEK resin, glass transition temperature 152°C, EVONIK.

[0039] Nano-inorganic compound with organic bio-based sodium sulfonate ester: Shanghai Magic Core New Material Technology Co., Ltd. 866 is an organic bio-based sodium sulfonate ester mixture compounded with spherical nano-inorganic matter, with a D50 of 35 microns.

[0040] Other processing aids: a combination of commonly used antioxidants, UV inhibitors, etc.; the experiment used equal amounts of Double Bond 1010 and 168 as antioxidants, and equal amounts of BASF 2020 and UV234 as UV inhibitors.

[0041] Uncarrier carbon black: carbon black masterbatch, carbon black concentration 30%-60%; the experiment used AS1040 from Ningbo Masterbatch Factory.

[0042] The material testing method is conventional technology, and specific examples are as follows.

[0043] Melt index: According to ISO 1133, 230°C, 3.8kg, required to be ≥2.0g / min.

[0044] Light transmittance: According to GB T 2410-2008, the ratio of the luminous flux passing through the sample to the luminous flux incident on the sample, expressed as a percentage, is required to be ≥90%. As a common sense, carbon black is omitted from the formula when conducting this test.

[0045] Vicat softening temperature: tested according to ISO 306, B50 method, heating rate 50℃ / h, requirement>105℃.

[0046] Gloss: At room temperature of 23±2℃, use a gloss meter to test the injection molding samples of the same mold. According to the standard GB / T 1743, the gloss at an angle of 20° is required to be ≥78 gloss (for high-gloss black materials, not applicable to transparent materials).

[0047] Appearance color: At room temperature of 23±2℃, use a colorimeter to test the injection molded samples of the same mold, and the L value must be ≤24.6 (visually achieve the effect of high-gloss black spray paint).

[0048] Pencil hardness: According to GBT 6739-2022, a pencil lead of a specified geometric shape is pressed downward on the surface of the paint film at a 45° angle under a load of (7.35 ± 0.15) N, and the pencil hardness of the paint film is measured by pushing the pencil on the paint film. The hardness of the pencil is gradually increased until visible defects appear on the surface of the paint film. The hardness of the hardest pencil that does not cause defects in the paint film is used to indicate the pencil hardness of the paint film; it is required to be ≥ 2H grade.

[0049] Product high temperature: The sample simulates the loading state, the storage temperature is 90℃±2℃, and the placement time is 240h. Take out the sample and place it at room temperature for 1h. According to the performance index requirements, there is no distortion, cracking, peeling, delamination, softening, hardening, blistering, whitening, wrinkling, powdering, melting, etc. The color change level is ≥4, the adhesion is 0-1, and all dimensions inside the assembly (gap, surface difference, contour) have no obvious changes.

[0050] Glass transition temperature Tg: According to the standard GB / T 19466-2008, the heating rate is 10℃ / min, the test temperature range is 23℃ to 200℃, and the glass transition temperature and peak number are determined according to the DSC curve. Tg is required to be ≥115℃ and there is only one peak.

[0051] Abrasion resistance: 1. Use a round double-sided tape to stick the friction head with a diameter of 3 / 4 inches to the friction disc with a diameter of 1 inch, and then assemble the friction disc to the weight rack; 2. Assemble the weight frame to the linear abraser, level the weight frame with a balancing weight, and add a 9N load to the weight frame; 3. Set the equipment parameters: friction rate 25 cycles / min, friction stroke 75 mm, friction cycle 10 times; 4. Use BYK three-angle gloss meter, select 20° angle, and test the gloss of the friction area; Calculate the gloss retention rate. Gloss retention rate = gloss after test / gloss before test * 100%. The gloss retention rate after the test is required to be ≥ 50%.

[0052] High and low temperature alternating test: 1 cycle 24h (including cooling and heating time); 10 cycles in total; temperature change rate 1.5℃ / min. Test cycle: 1: -30℃ *4h; 2: 95℃* 4h; 3: 38℃* 95%RH*16h. Parts are required to be free of deformation.

[0053] Comparison Example The above test method is used to test the performance of existing commercially available PMMA materials for automotive trim panels, as follows: Embodiment 1

[0054] Using a twin-screw extruder, 78.45Kg CM205, 20Kg bio-based polycarbonate resin (No. 2 modifier), 0.25Kg nano-inorganic composite organic bio-based sodium sulfonate, 0.4Kg antioxidant, 0.4Kg anti-ultraviolet agent, and 0.5Kg carbon black are conventionally mixed in a high-speed mixer, and then directly enter the twin-screw extrusion melt processing granulation to obtain modified heat-resistant PMMA. The product has a melt index of 5.2 g / min, a transmittance of 91.2%, a Vicat softening temperature of 111.7℃, a glossiness of 83.6, a high-gloss black L value of 23.3, and a pencil hardness of 2H, which can meet the product high-temperature test, Tg (121.2℃) One peak, qualified wear resistance, high and low temperature alternation results meet the requirements, and there is no deformation of parts. The comprehensive performance can be used to produce automotive trim, turn signal and other materials.

[0055] The twin-screw equipment used has a diameter of 55 mm, a rotation speed of 800 rpm, a temperature of 210-260°C, and is processed into granules.

[0056] See also Figure 1 , which is a conventional sample preparation photo of the above-mentioned modified heat-resistant PMMA (carbon black omitted), has excellent light transmittance.

[0057] See also Figure 2 , which is a conventional sample preparation photo of the above-mentioned modified heat-resistant PMMA, has an excellent high-gloss black effect.

[0058] See also Figure 3 , which is a photo of the conventional sample preparation of the above-mentioned modified heat-resistant PMMA. There is no deformation at the injection molding inlet and other parts.

[0059] Comparative Example 1 Omitting Nano-Inorganic Composite Organic Bio-Based Sodium Sulfonate Using a twin-screw extruder, 78.7Kg CM205, 20Kg bio-based polycarbonate resin (No. 2 modifier), 0.4Kg antioxidant, 0.4Kg UV inhibitor, and 0.5Kg carbon black were mixed in a high-speed mixer and directly sent to a twin-screw extruder for melting and granulation to obtain modified heat-resistant PMMA. The Vicat softening temperature of this product is 110.3℃, which can meet the high-temperature test of the product, with a peak of Tg119℃. The high and low temperature alternation results meet the requirements, but the glue inlet is deformed. See Figure 4 , is a photo of the conventional sample preparation of the modified heat-resistant PMMA, which is an unqualified product.

[0060] The twin-screw equipment used has a diameter of 55 mm, a rotation speed of 800 rpm, a temperature of 210-260°C, and is processed into granules.

[0061] Comparative Example 2 Omitting Bio-based Polycarbonate Resin (Modifier No. 2) Using a twin-screw extruder, 98.45Kg CM205, 0.25Kg nano-inorganic composite organic bio-based sodium sulfonate, 0.4Kg antioxidant, 0.4Kg anti-ultraviolet agent, and 0.5Kg carbon black were conventionally mixed in a high-speed mixer and then directly sent into a twin-screw extruder for melt processing and granulation to obtain modified PMMA. The Vicat was insufficient, and the parts were deformed by alternating high and low temperature conditions, which did not meet the requirements.

[0062] The twin-screw equipment used has a diameter of 55 mm, a rotation speed of 800 rpm, a temperature of 210-260°C, and is processed into granules.

[0063] Comparative Example 3 Modifier No. 1 Using a twin-screw extruder, 78.45Kg CM205, 20Kg Lotte 1220 (No. 1 modifier), 0.25Kg nano-inorganic composite organic bio-based sodium sulfonate, 0.4Kg antioxidant, 0.4Kg anti-ultraviolet agent, and 0.5Kg carbon black are conventionally mixed in a high-speed mixer and directly enter the twin-screw extruder for melt processing and granulation to obtain modified heat-resistant PMMA. The Vicat softening temperature of this product is 109.2℃, which can meet the product high temperature test, has qualified wear resistance, a light transmittance of 13.2% and a birefringent appearance. It cannot be used to produce materials such as automotive trim panels and turn signals.

[0064] The twin-screw equipment used has a diameter of 55 mm, a rotation speed of 800 rpm, a temperature of 210-260°C, and is processed into granules.

[0065] Comparative Example 4 Modifier No. 3 Using a twin-screw extruder, 78.45Kg CM205, 20Kg BP-356M (No. 3 modifier), 0.25Kg nano-inorganic composite organic bio-based sodium sulfonate, 0.4Kg antioxidant, 0.4Kg anti-ultraviolet agent, and 0.5Kg carbon black are conventionally mixed in a high-speed mixer, and then directly enter the twin-screw extruder for melting and granulation to obtain modified heat-resistant PMMA. The Vicat softening temperature of this product is 106.7℃, and the appearance shows silver wire and water splashes, which does not meet the product high-temperature test, the wear resistance is unqualified, and the parts are deformed at high and low temperatures, which does not meet the requirements. It cannot be used to produce materials such as automotive trim panels and turn signals.

[0066] The twin-screw equipment used has a diameter of 55 mm, a rotation speed of 800 rpm, a temperature of 210-260°C, and is processed into granules.

[0067] Comparative Example 5 Modifier No. 4 Using a twin-screw extruder, 78.45Kg CM205, 20Kg PEEK resin (No. 4 modifier), 0.25Kg nano-inorganic composite organic bio-based sodium sulfonate, 0.4Kg antioxidant, 0.4Kg anti-ultraviolet agent, and 0.5Kg carbon black are conventionally mixed in a high-speed mixer and directly enter the twin-screw extruder for melting and granulation to obtain modified heat-resistant PMMA. The Vicat softening temperature of this product is 112.2℃, which can meet the product high temperature test, Tg three peaks, wear resistance qualified, appearance birefringence, and it cannot be used to produce automotive trim, turn signal and other materials.

[0068] The twin-screw equipment used has a diameter of 55 mm, a rotation speed of 800 rpm, a temperature of 210-260°C, and is processed into granules.

[0069] Comparative Example 6 Using a twin-screw extruder, 78.45Kg CM205, 20Kg bio-based polycarbonate resin (modifier No. 2), 0.25Kg nano-silicon dioxide (specific surface area 170-200m 2 / g), 0.4Kg antioxidant, 0.4Kg anti-ultraviolet agent, and 0.5Kg carbon black are conventionally mixed in a high-speed mixer and directly enter into a twin-screw extruder for melt processing and granulation to obtain modified heat-resistant PMMA, which has an unsatisfactory surface, poor light transmittance, and white particles on the surface. It cannot be used to produce materials such as automobile trim panels and turn signals.

[0070] The twin-screw equipment used has a diameter of 55 mm, a rotation speed of 800 rpm, a temperature of 210-260°C, and is processed into granules. Embodiment 2

[0071] Using a twin-screw extruder, 73.45Kg CM205, 25Kg bio-based polycarbonate resin (No. 2 modifier), 0.25Kg nano-inorganic composite organic bio-based sodium sulfonate, 0.4Kg antioxidant, 0.4Kg anti-ultraviolet agent, and 0.5Kg carbon black are conventionally mixed in a high-speed mixer and directly enter the twin-screw extruder for melting and granulation to obtain modified heat-resistant PMMA. This product can meet the product high-temperature test, wear resistance is qualified, high and low temperature alternation results meet the requirements, and the comprehensive performance can be used to produce automotive trim, turn signal and other materials.

[0072] The twin-screw equipment used has a diameter of 55 mm, a rotation speed of 800 rpm, a temperature of 210-260°C, and is processed into granules. Embodiment 3

[0073] Using a twin-screw extruder, 78.5Kg CM205, 20Kg bio-based polycarbonate resin (No. 2 modifier), 0.2Kg nano-inorganic composite organic bio-based sodium sulfonate, 0.4Kg antioxidant, 0.4Kg anti-ultraviolet agent, and 0.5Kg carbon black are conventionally mixed in a high-speed mixer and directly sent to a twin-screw extruder for melt processing and granulation to obtain modified heat-resistant PMMA. This product can meet the product high-temperature test, wear resistance is qualified, high and low temperature alternation results meet the requirements, and the comprehensive performance can be used to produce automotive trim, turn signal and other materials, see Figure 5 , which is a photo of the conventional sample preparation of the modified heat-resistant PMMA. There is no deformation in the glue inlet and other parts.

[0074] The twin-screw equipment used has a diameter of 55 mm, a rotation speed of 900 rpm, a temperature of 210-260°C, and is processed into granules. Embodiment 4

[0075] Using a twin-screw extruder, 78.4Kg CM205, 20Kg bio-based polycarbonate resin (No. 2 modifier), 0.3Kg nano-inorganic composite organic bio-based sodium sulfonate, 0.4Kg antioxidant, 0.4Kg anti-ultraviolet agent, and 0.5Kg carbon black are conventionally mixed in a high-speed mixer and directly enter the twin-screw extruder for melting and granulation to obtain modified heat-resistant PMMA. This product can meet the product high-temperature test, wear resistance is qualified, high and low temperature alternation results meet the requirements, and the comprehensive performance can be used to produce automotive trim, turn signal and other materials.

[0076] The twin-screw equipment used has a diameter of 60 mm, a rotation speed of 800 rpm, a temperature of 210-260°C, and is processed into granules.

[0077] At present, materials such as automobile trims and turn signals are modified PMMA by spray-free painting, but they cannot meet the customer's requirements for temperature deformation resistance, resulting in deformation during use. The present invention mainly solves the problem of insufficient heat resistance, provides a modified heat-resistant PMMA and its preparation method and application, and prepares the key properties of modified PMMA heat-resistant materials: transparency (light transmittance above 90%), high glass transition temperature Tg (Tg not less than 120°C), good colorability (easy to color and no birefringence), pencil hardness up to 2H, and has good temperature alternating resistance, which has made significant technical progress compared with the existing PMMA materials used in production.

Claims

1. A method for preparing a modified heat-resistant PMMA, comprising the following steps: melt-mixing a PMMA resin, a modifying material, and an additive to obtain a modified heat-resistant PMMA, characterized in that: The modified materials include bio-based polycarbonate resin and nano-inorganic composite organic bio-based sodium sulfonate.

2. The method for preparing the modified heat-resistant PMMA according to claim 1, characterized in that: The mass ratio of PMMA resin, bio-based polycarbonate resin, nano-inorganic composite organic bio-based sodium sulfonate and additives is (70-85): (15-30): (0.1-0.5): (0.5-1.5).

3. The method for preparing the modified heat-resistant PMMA according to claim 1, characterized in that: The modified material consists of bio-based polycarbonate resin and nano-inorganic composite organic bio-based sodium sulfonate.

4. The method for preparing the modified heat-resistant PMMA according to claim 1, characterized in that: The auxiliary agent includes an antioxidant and a weathering agent, or the auxiliary agent includes an antioxidant, a weathering agent and a pigment.

5. Modified heat-resistant PMMA prepared by the method for preparing modified heat-resistant PMMA according to claim 1.

6. Use of the modified heat-resistant PMMA according to claim 1 in the preparation of heat-resistant plastics.

7. Use of the modified heat-resistant PMMA according to claim 1 in the preparation of heat-resistant transparent materials.

8. Use of the modified heat-resistant PMMA according to claim 1 in the preparation of heat-resistant automotive materials.

9. A heat-resistant plastic, the raw materials for its preparation include the modified heat-resistant PMMA according to claim 1.

10. A heat-resistant automobile material, wherein the raw materials for preparing the material include the modified heat-resistant PMMA according to claim 1.